Lyme neuroborreliosis with encephalitis: A rare case - Simone Bruhn Rosendahl; Pernille Ravn; Anne-Mette Lebech; Christian Peter Midtgaard Stenør (IDCases, 2023)
Encephalitis caused by Borrelia burgdorferi sensu lato is a rare clinical manifestation of Lyme neuroborreliosis and only in few cases have brain parenchymal inflammation been documented. Here, we present a case of Lyme neuroborreliosis with encephalitis with significant parenchymal inflammation on magnetic resonance imaging (MRI) in an immunosuppressed patient.